2013
DOI: 10.1016/j.bbamem.2012.12.005
|View full text |Cite
|
Sign up to set email alerts
|

P-glycoprotein is fully active after multiple tryptophan substitutions

Abstract: P-glycoprotein (Pgp) is an important contributor to multidrug resistance of cancer. Pgp contains eleven native tryptophans (Trps) that are highly conserved among orthologs. We replaced each Trp by a conservative substitution to determine which Trps are important for function. Individual Trp mutants W44R, W208Y, W132Y, W704Y and W851Y, situated at the membrane surface, revealed significantly reduced Pgp induced drug resistance against one or more fungicides and/or reduced mating efficiencies in Saccharomyces ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 59 publications
2
21
0
Order By: Relevance
“…This selection scheme is based on the ability to convey resistance of the yeast to fungicides as well as export a-factor pheromone and restore mating in the otherwise sterile yeast by complementing for Ste6, a Pgp yeast homologue [34,39]. Mating, by itself, is a stringent test of mutant function as we previously demonstrated [40]. The customized selection scheme was designed to identify mutants that could transport multiple, structurally diverse substrates and preserve polyspecificity, an important quality of Pgp.…”
Section: Resultsmentioning
confidence: 99%
“…This selection scheme is based on the ability to convey resistance of the yeast to fungicides as well as export a-factor pheromone and restore mating in the otherwise sterile yeast by complementing for Ste6, a Pgp yeast homologue [34,39]. Mating, by itself, is a stringent test of mutant function as we previously demonstrated [40]. The customized selection scheme was designed to identify mutants that could transport multiple, structurally diverse substrates and preserve polyspecificity, an important quality of Pgp.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the authors demonstrated that the F1086A mutation disrupted the NBD/TMD coupling because F1086A successfully inhibited ATP‐dependent cross‐linking of the mutant protein T333C/L975C, located at the extracellular ends of TM helices 6 and 12 . Another study also pointed out the importance of TMD/NBD interdomain communication by showing that mutations in tryptophans located at the coupling helices (W158F/W799F) severely impaired mating efficiencies in yeast colonies (Table ) …”
Section: Targeting Signal Transductionmentioning
confidence: 98%
“…122 Another study also pointed out the importance of TMD/NBD interdomain communication by showing that mutations in tryptophans located at the coupling helices (W158F/ W799F) severely impaired mating efficiencies in yeast colonies ( Table 2). 132 Two other mutations in ICH1 (D164C) and ICH3 (D805C) were also described to have significant alterations in P-gp function. While D805C completely abolished drug transport, the double mutant D164C/D805C showed about 70% decrease in daunorubicin and [N-ε(4-nitrobenzofurazan-7-yl)-d-Lys 8 ]-cyclosporine A (NBD-CsA) transport, only partially effluxing calcein-AM (~60%).…”
Section: Targeting Signal Transductionmentioning
confidence: 99%
“…Positive clones were then screened in two different fungicidal drugs, FK506 and doxorubicin. This selection scheme was designed to identify mutants that could preserve polyspecific drug transport, an important quality of Pgp, based on its ability to export the a-mating factor and convey fungicidal resistance to yeast against two drugs 74,78,79 . The blocks from clones that mated and were active in both drug assays were sequenced to identify Trp-free clones.…”
Section: Resultsmentioning
confidence: 99%
“…The first attempt to create Trp-free Pgp by replacing all 11 Trps by Phe ("All-F") 73 gave a transporter with minimal function and impaired expression, making it unusable as a tool for further studies. Subsequent experiments showed that multiple Pgp Trps could be successfully removed, but also suggested that aromatic amino acids may not be the ideal substitute at several Pgp Trp locations 74 . In the context of a large integral membrane protein, Trps can be found in a variety of local environments, as demonstrated by Pgp.…”
mentioning
confidence: 99%